Rodzaje urazów i częstość ich występowania w siatkówce wyczynowej kobiet = Types of injuries and frequency of occurrence in women's volleyball - Wójcik, Gustaw; Skalska-Izdebska, Renata; Śliwińska, Ewa; Szulc, Anna (Journal of Education, Health and Sport, 2016)
Wójcik Gustaw, Skalska-Izdebska Renata, Śliwińska Ewa, Szulc Anna. Rodzaje urazów i częstość ich występowania w siatkówce wyczynowej kobiet = Types of injuries and frequency of occurrence in women's volleyball. Journal of Education, Health and Sport. 2016;6(12):98-108 eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192457 http://ojs.ukw.edu.pl/index.php/johs/article/view/4036 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 03.12.2016. RODZAJE URAZÓW I CZĘSTOŚĆ ICH WYSTĘPOWANIA W SIATKÓWCE WYCZYNOWEJ KOBIET TYPES OF INJURIES AND FREQUENCY OF OCCURRENCE IN WOMEN'S VOLLEYBALL Gustaw Wójcik1, Renata Skalska-Izdebska2, Ewa Śliwińska2, Anna Szulc3 1Państwowa Szkoła Wyższa im. Papieża Jana Pawła II w Białej Podlaskiej. Wydział Nauk o Zdrowiu i Nauk Społecznych, Katedra Kultury Fizycznej i Fizjoterapii 2Uniwersytet Rzeszowski, Wydział Medyczny, Instytut Fizjoterapii 3Uniwersytet Medyczny w Lublinie, Wydział Nauk o Zdrowiu, Katedra Rehabilitacji STRESZCZENIE Wstęp: Sport wyczynowy od zawsze był nieodłącznie związany z kontuzjami i uszkodzeniami narządu ruchu. Medialna promocja sportu oraz jego komercjalizacja zmusiły zawodowych sportowców do znoszenia obciążeń treningowych przekraczających możliwości organizmu. W celu osiągnięcia jak najlepszych wyników, zaczęto wprowadzać do sportu wyczynowego coraz młodszych zawodników, których organizmy trudno znoszą nadmierne obciążenia treningowe. Ciągła pogoń za sukcesem, realizowana zgodnie z zasadą „cel uświęca środki”, doprowadziła do gwałtownego wzrostu liczby urazów i uszkodzeń narządu ruchu od drugiej połowy XX wieku. Cel pracy: celem pracy było zbadanie, jaki rodzaj urazu występował najczęściej wśród zawodowych siatkarek, jakiej okolicy ciała najczęściej dotyczył oraz czy powodował wystąpienie dysfunkcji w uszkodzonej części ciała. Materiał i metody: Badanie przeprowadzono na grupie 31 zawodowych siatkarek trenujących w polskich klubach orlenligowych i pierwszoligowych. W celu oceny rodzaju i częstotliwości najczęściej występujących urazów posłużono się ankietą autorską. W opracowaniu wyników wykorzystano program Statistica 10.0 Wyniki: Wśród badanych zawodniczek 96,7% doznało w swojej karierze urazu. Większość kontuzji dotyczyła stawów w tym najwięcej skokowego (67,7%) i kolanowego (48,3%). Wnioski: Najczęściej występującym urazem wśród siatkarek trenujących wyczynowo były skręcenia stawu. Obszarem ciała, najczęściej ulegającym kontuzjom, był staw skokowy. Słowa kluczowe: uraz sportowy, piłka siatkowa, zwichnięcia, skręcenia ABSTRACT Background: Professional sport is always integrally connected with injuries of body. Media promotion of sport and its commercialisation forces players to endure training load, which crosses their bodies possibilities. To achieving the best scores, people was starting to bring younger players to proffesional sport. Their bodies wasn’t completely formed and not be able to match excessive training load. Unstoppable pursuit of success led to sudden increase of sport injuries since the second half of 20th century. Aim: The aim of this thesis is examination which kind of injury is generally appearance and in which part of the body it generally occurs. Material and methods: The thesis is conducted on a group of 31 professional women volleyball players from Orlenliga and first league. To assessment the kind and frequency of the most common injuries the own questionnaire has been used. In elaboration of results, the Statisctica 10.0 program has been used. Results: Among professional women volleyball players 97,6% had an injury. Injuries mostly concern joints, especially ankle and knee. Conclusion: The most common injuries in professional women volleyball is joint sprains. Injuries mostly occur in the ankle. Key words: sport injury, volleyball, dislocations, torsion joint.